Stakeholders' perceptions on how schools influence the career development of learners with intellectual disabilities - Miya, Paballo (University of Pretoria, 2021)
Many learners with intellectual disabilities in mainstream schools are awaiting possible placements in special schools. In some instances, when placement becomes unsuccessful learners remain in mainstream schools which becomes the schools’ responsibility to find ways to support them in a manner that maximises their learning potential and provides direction regarding career development. This study explored parents, teachers and principals’ perceptions about intellectual disability and its influence on career development. The Critical Disability Theory guided this study as it was aimed at discovering the factors which influence the implementation of career development in schools. A qualitative approach was followed to collect data from 25 participants consisting of 2 principals, 14 teachers and 9 parents. Data was collected in the form of interviews, focus group discussions, and demographic questionnaires. Thematic analysis was used to analyse the data. Findings indicated that stakeholders had limited knowledge about career development services. Parents concluded that schools could put more effort into supporting learners with intellectual disabilities, and that teachers could put more effort to academically support learners. Stakeholders were optimistic that learners with intellectual disabilities would be able to participate in the labour market, provided that they are taught work related skills at an early age. It was recommended that stakeholders make efforts to obtain knowledge about the career development services available and provide information to learners in that regard; make career development services accessible, and to teach learners with disabilities practical work skills enabling them to participate in the labour force post-school. === Dissertation (MEd)--University of Pretoria, 2020. === Educational Psychology === MEd === Unrestricted